1994
DOI: 10.1007/bf02244862
|View full text |Cite
|
Sign up to set email alerts
|

Platelet intracellular calcium in patients with recurrent affective disorders

Abstract: Forty-four subjects with a history of a major recurrent affective disorder in remission and who were either on no medication or taking a single dose of psychotropic medication were conscripted together with matched controls. The fluorescent indicator fura 2 was used to measure intracellular calcium in platelets and estimations were made of total serum and ionised calcium as well as of whole blood serotonin. Intracellular calcium was measured in the resting state as well as after stimulation with thrombin, plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 60 publications
3
7
0
Order By: Relevance
“…The Ca mobilization in bipolar disorder was larger than that in control and unipolar depression, but it was not statistically significant. Enhanced platelet intracellular Ca response to 5-HT in untreated affective disorder is a relatively common finding except one report (Bothwell et al, 1994). In our previous report, both unipolar and bipolar disorder patients showed higher Ca response to 5-HT compared with control (Kusumi et al, 1994).…”
Section: Discussionsupporting
confidence: 39%
“…The Ca mobilization in bipolar disorder was larger than that in control and unipolar depression, but it was not statistically significant. Enhanced platelet intracellular Ca response to 5-HT in untreated affective disorder is a relatively common finding except one report (Bothwell et al, 1994). In our previous report, both unipolar and bipolar disorder patients showed higher Ca response to 5-HT compared with control (Kusumi et al, 1994).…”
Section: Discussionsupporting
confidence: 39%
“…Other studies involving a mix of BPD patients have also found elevated basal platelet and lymphocyte calcium concentrations [233][234][235] and elevated B-lymphoblast calcium [236]. In contrast, however, there are also several reports of normal cellular calcium levels in manic BPD patients [229,230,237,238], depressed BPD patients [227,229,230,239,240], and in lithium-treated BPD patients [227,228,237,241,242].…”
Section: Mdd + Dep Bpdsupporting
confidence: 40%
“…In BPD patients in various mood states, on a variety of medications, an enhanced calcium response has also been found in platelets in response to agonist stimulation [235,247,248]. It is possible these abnormal responses may be normalized by lithium treatment, since in platelets of euthymic BPD patients taking lithium there is a normal calcium response [227,228,230,237,241].…”
Section: Agonist-stimulated Levelssupporting
confidence: 39%
“…Summarizing, patients with a depressive disorder show signs of a hyperactive platelet 5-HT 2A receptor signal transduction system as measured by increased platelet calcium mobilization after stimulation of the platelet with serotonin. In the above-mentioned studies, patients treated with an antidepressant still appeared to have an increased 5-HT 2A receptor response to stimulation with serotonin, although attenuated (46,82,84).…”
Section: Coronary Events and 5-ht 2a Receptormentioning
confidence: 42%
“…Post 5-HT 2A receptor response can be studied by quantification of serotonin-induced calcium mobilization. Although some studies found no significant difference (50,84), evidence for significantly augmented platelet calcium mobilization in response to serotonin in patients with major depression as compared with controls is abundant (44 -46, 51, 85-90). Increased platelet 5-HT 2A receptor sensitivity was found in depressed patients without antidepressant medication (51,(85)(86)(87)(88)(89)(90) as assessed by calcium response to serotonin stimulation.…”
Section: Coronary Events and 5-ht 2a Receptormentioning
confidence: 42%